Lobbying of Qatar's Interests in the United States and the Qatar Diplomatic Crisis - D. B. Grafov (Vestnik MGIMO-Universiteta, 2020)
Qatar lobbied its interests in the US in order to ease tensions with the Gulf c tries which declared a blockade on Qatar in June 2017. Saudi Arabia, the United Arab Emirates, Bahrain and Egypt accused Qatar of supporting terrorism, demanded to break off all ties with Iran and to close the Turkish military base on its territory. The article analyses the lobbying campaign against the blockade. It uses the facts and data disclosed by the consulting and lobbying firms according to “The Foreign Agents Registration Act of 1938” and “The Lobbying Disclosure Act of 1995”. Three main conclusions are drawn: 1) The US is not interested in settlement of dispute through the support of one party. The White House prefers the “divide and rule” strategy. 2) There is little chance of successful lobbying in the US for any state that cooperates with Iran. 3) The balance-of-power approach in analysing of the development of Qatari-Saudi crisis shows that attempt of the both parties to “buck-pass” by one superpower is uneffisient. The reason is that both Qatar and Saudi coalition act like US's clients. Although Qatar is not as powerful as its rivals, but it uses the “defensive realism” strategy, that allows it to disrupt aggressive efforts and increase the costs of the Saudi coalition.